THE INDONESIAN LINGUISTIC VALIDATION OF THE URINARY STENT RELATED HEALTH QUESTIONNAIRE - Simanjuntak, Dikes; Pahria, Tuti; Platini, Hesti; Sihombing, Aaron Tigor (Indonesian Urological Association, 2024)
Objective: To validate the Indonesian version of the urinary stent related health (UriSteRH) questionnaire. Material & Methods: The Indonesian version of the UriSteRH was developed with multistep process by urologist, two nursing lecturers and two independent translators. A total 13 patients with indwelling DJ Stent completed the Indonesian UriSteRH questionnaires on the 30th day after Stenting. The reliability of the Indonesian version was evaluated using Cronbach’s alpha test. Domain structures were examined by using Pearson correlation coefficient (R). Results: Urinary pain, body pain, physical activity, social life, mental health, sexual activity and quality of life showed good internal consistency. There were strong correlations of physical activity (r=0.851) and social life (r=0.815) with the quality of life (r=0.736). In addition, there were moderate correlation of mental health general (r=0.676) related to urinary pain (r=0.612) and body pain (r=0.567). However, sexual activity had a lower correlation (r=0.456). Conclusion: The Indonesian version of UriSteRH is a reliable and valid instrument to evaluate health and quality of life in patients with indwelling DJ Stent. Keywords: DJ Stent, indonesian validation, questionnaire, urinary stent related health .